What are the Top 10 Unanswered Questions in Molecular Plant-Microbe Interactions? - Harris, Jeanne M. (2020)
The past few decades have seen major discoveries in the field of molecular plant-microbe interactions. As the result of technological and intellectual advances, we are now able to answer questions at a level of mechanistic detail that we could not have imagined possible 20 years ago. The MPMI Editorial Board felt it was time to take stock and reassess. What big questions remain unanswered? We knew that to identify the fundamental, overarching questions that drive our research, we needed to do this as a community. To reach a diverse audience of people with different backgrounds and perspectives, working in different areas of plant-microbe interactions, we queried the more than 1,400 participants at the 2019 International Congress on Molecular Plant-Microbe Interactions meeting in Glasgow. This group effort resulted in a list of ten, broad-reaching, fundamental questions that influence and inform our research. Here, we introduce these Top 10 unanswered questions, giving context and a brief description of the issues. Each of these questions will be the subject of a detailed review in the coming months. We hope that this process of reflecting on what is known and unknown and identifying the themes that underlie our research will provide a framework to use going forward, giving newcomers a sense of the mystery of the big questions and inspiring new avenues and novel insights.